Diagnostic and interactive systems of strategic risk indicators of management accounting in innovation activities - V.M. Ivankov (Проблеми теорії та методології бухгалтерського обліку, контролю і аналізу, 2017)
The article deals with the investigation of main trends of the development of innovative activity in Ukraine during last years. It is determined that the quantity of innovatively active Ukrainian enterprises is growing, and this trend continues existing. The statistic indicators of innovative activity of industrial enterprises for 2014-2015 years are investigated. It is determined that the world market of technologies remains the engine of economic growth in modern economic conditions. It is proved, that the reliable information provision of needs in management of innovative processes requires argumentation of new accounting technologies that must consider risk nature of innovations and main trends of the development of instruments of the strategic management accounting. The characteristics of diagnostic and interactive systems of indicators are investigated and it is identified that both systems are interactive and may function simultaneously for control of realization of chosen strategy (diagnostic system) and for testing of non-standard situations in conditions of uncertainty and risk (interactive system). It is identified, that the peculiarity of interactive systems is still the adaptation of one or two indicators of diagnostic systems by means of focusing on influence of uncertainty and risk on the results of realization of strategic goals or on the indicators of risk-result. Taking into consideration the risk nature of innovative activity, the author investigates the approaches upon the possible usage of instruments of risk-management in the concepts of management accounting, namely balanced scorecard. It is identified that the modern approach provides the inspection of strategic goals realization as the chances, and the risks as factors, that inhibit their achievement. This allows determining the influence of all the identified risks on deviations from the target (normative) values of strategic indicators, which are the expression of a certain strategic goal. It is proved that the most effective approach is the orientation towards the indicators of risk-factors, which allow to track the early signs of risk situation (event) appearance with uncertain influence and probability, that is, the early signals of the risk. In the capacity of conditions of recognizing separate strategic indexes as risk-indicators (advancing (early) indicators) the author proposes to conduct the procedure of comparison by means of their possible recognition as factors of creation of the value of capital of the enterprise and their simultaneous recognizing as the conditions, which manifest causes (sources) of a risk situation (event). This approach characterizes strategic risk-indicators as the complex early indicators of common (integrated) appraisal of factors of creation of the enterprise capital value that is under the influence of risk. This allows to propose the inception of combined system of strategic risk-indicators, which provides the simultaneous coordinated usage of both systems: the diagnostic system for assessment and recognizing common (nonspecific) risk, inherent in all entrepreneurial activity) and the interactive system for assessment and recognizing individual (specific) risk of innovative activity.